Detection of Sex Steroid Expressions in Benign Versus Malignant Adrenal Tumor Tissue Homogenates With Western Blot Analysis - Oguz, Seda Hanife (J Endocr Soc, 2021)
Background: Adrenocortical cancer (ACC) is a rare tumor with poor prognosis. The prognostic value of sex steroid expressions in ACC, was firstly shown by our group with immunohistochemistry staining in paraffin embedded blocks (1). Aim: To detect the presence of sex steroid expressions in different types of adrenal fresh tissue samples by Western Blot method. Method: Adrenal fresh tissue samples were isolated from benign (patient 1: adrenal hemangioma, n: 1 intratumoral + 1 extratumoral tissue samples) and malignant tumors (patient 2: ACC, n: 4 intratumoral tissue samples). Expressions of estrogen receptor alpha (Erα), progesterone receptor A (PR), androgen receptor (AR) and aromatase proteins were investigated using Western Blot method in the tissue lysates obtained. Monoclonal antibodies that recognize a single determinant of the obtained denatured proteins with high affinity and specificity were used. GAPDH was used as control protein. After the primary antibody incubation, the incubation phase was started with the secondary antibody produced against the organism in which HRP (Horseradish Peroxidase) conjugated primary antibody was produced in order to visualize the primary antibody. ECL (Enhanced chemiluminescence) solution containing luminol, which is the substrate of the peroxidase enzyme contained in HRP conjugated to the secondary antibody, was used to enable the proteins to which the secondary antibody was bound to emit chemoluminescence. Finally, the densitometric densities of the bands obtained by chemiluminescence imaging were determined. Results: Expression of ER, AR, PR and aromatase was demonstrated in fresh tissue samples obtained from ACC, adrenal hemangioma and normal adrenal cortex. PR expression was higher in ACC lysates. ER and AR expressions were higher in hemangioma and normal adrenal cortex, respectively. Aromatase expression was also higher in adrenal hemangioma while similar in cancerous and normal adrenal tissue samples. Conclusions: We have demonstrated the dissimilarities between the expressions of sex steroid receptors and aromatase by using Western Blot method in fresh tissue samples obtained from different types of adrenal masses, including ACC. It would be possible to develop an in vitro experimental ACC model that can test the effect of sex steroid receptor ligands on tumor growth in order to clarify their role in adrenal tumorigenesis. Reference:1. Oguz SH, Sokmensuer C, Bayraktar M, Dagdelen S. Estrogen, progesterone, and androgen receptor expressions predict the prognosis for adrenocortical carcinoma. Endocrine Society’s Annual Meeting, 23–26 March 2019, New Orleans - USA. Journal of the Endocrine Society, Volume 3, Issue Supplement_1, April-May 2019, SUN-352.